2021
DOI: 10.1158/1535-7163.mct-20-1125
|View full text |Cite
|
Sign up to set email alerts
|

Silylation of Deoxynucleotide Analog Yields an Orally Available Drug with Antileukemia Effects

Abstract: DNA methyltransferase inhibitors have improved the prognosis of myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). However, because these agents are easily degraded by cytidine deaminase (CDA), they must be administered intravenously or subcutaneously. Recently, two orally bioavailable DNA methyltransferase inhibitors, CC-486 and ASTX727, were approved. In previous work, we developed 5-O-trialkylsilylated decitabines that resist degradation by CDA.However, the effects of silylation of a deoxynucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Similar to DAC ( 11 ), OR21 monotherapy inhibited growth of AML cell lines (HL60, SKM1, THP1, KG1a, and Kasumi-1) in a dose-dependent manner ( Supplementary Fig. S1 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar to DAC ( 11 ), OR21 monotherapy inhibited growth of AML cell lines (HL60, SKM1, THP1, KG1a, and Kasumi-1) in a dose-dependent manner ( Supplementary Fig. S1 ).…”
Section: Resultsmentioning
confidence: 95%
“…Thus, we did not test the DAC plus Ven in vivo . Moreover, OR21 is an effective treatment for AZA-resistant leukemia in vi vo ( 11, 30 ). Hence, the combination of Ven plus OR21 may benefit patients with AML, including AZA-resistant AML, thereby replacing the standard therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although combination therapy is often associated with side effects, we demonstrated that the hematotoxicity of combination treatment with OR21 and EZH2 was not greater than that of single treatment ( Figure 6 D). OR21 has lower hematotoxicity than DAC, 24 , 25 , 26 suggesting that a combination with OR21 rather than DAC could be clinically beneficial.…”
Section: Discussionmentioning
confidence: 99%
“… 24 OR21 is a silylated derivative of DAC that is resistant to cytidine deaminase and can be administered orally. 24 , 25 , 26 These previous results led us to investigate the effect of combination treatment with DNA demethylating agents and EZH2 inhibitors in patients with ATL.…”
Section: Introductionmentioning
confidence: 99%